St. Vitus’ Day Among Slovenes - Jezernik, Božidar (Wydawnictwo Naukowe UAM, 2013)
National holidays play an important role in the formation of common memories of the past, as they are the very sign that marks historical events and figures that must be known to all citizens, thereby establishing the symbolic unity of all the members of the nation. The holidays of the Kingdom of Serbs, Croats and Slovenes emphasized the national unity of the ‘three tribes’, and St. Vitus’ Day was thus added to the otherwise short list. At the beginning of December 1919, the Minister of the Interior of the newly formed national state of the ‘nation with three names’ declared three new national holidays: 1 December as the ‘day of the unification of our „nation with three names”’; St. Peter’s Day on 12 July as the birthday of King Peter I.; and St. Vitus’ Day on 28 June as a ‘day of commemoration for those who had died fighting for the faith and the homeland’. The use of Serbian symbols and cultural forms in commemorations in the new nation-state meant that the commemorations in the state of the ‘nation with three names’ glorified the Serbian sacrifices and suffering, but denied the contribution of Croats and Slovenes to the establishment of the state community. Together with the provisions and spirit of the St. Vitus’ Day Constitution, the glorification of Serbian mythology as the national mythology of the ‘nation with three names’, which was meant to be the foundation stone for the bright future of the unified nation, became more and more of a stumbling stone with each passing day.
Keywords: Nation with Three Names (Kingdom of Serbs, Croats and Slovenes); National holidays; the Politics of Commemoration; Religion and Nation-State; St. Vitus Day; St. Vitus Day’s Heroes and Villains